Comparison of two surgical treatments for proximal femur fracture in elderly obese patients - Kh. Ch. Khan'; I. F. Akhtyamov; S. A. Ardashev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The choice of treatment methods for patients with fractures of the trochanteric region of the femur, as well as specific surgical tactics, is justified. According to a number of researchers, hip arthroplasty is an alternative to osteosynthesis in such injuries, especially in patients with limited functional capacity and a poor medical history. The primary results of endoprosthesis and intramedullary blocked fixation constructions in elderly patients with obesity were compared. Purpose of the study. To evaluate the clinical efficacy of intramedullary osteosynthesis and endoprosthesis in obese patients with vertebral fractures of the proximal femur. Materials and methods. The study was carried out on the basis of the Republican Clinical Hospital of the Ministry of Health of the Republic of Tatarstan. A total of 76 patients aged 66 to 91 years were operated on. Two techniques were used in the treatment. 46 patients who underwent primary hip arthroplasty (THA) and 30 patients who underwent blocked intramedullary osteosynthesis (BIOS) with proximal femoral nail of gamma-nail type. Results. 1. A comparative study with a relatively small sample showed that there was no statistically significant difference in the duration of surgery between patients with normal BMI and obese patients with different surgical approaches. 2. Blood loss rates in both groups were less than the critical level (p < 0.05). The study expectedly confirmed that the higher the patient's BMI, the longer the duration of surgery and the greater the blood loss. 3. The presented material suggests that arthroplasty can be used for vertebral fractures of the proximal femur if there are no relevant surgical contraindications. 4. The relative difficulty of performing blocked intramedullary pinning, difficulty in activating and rehabilitating obese patients, and risks of early loading of the injured limb lead to the search for alternative methods of surgical treatment of acetabular femoral fractures. Using the advantages of hip arthroplasty is the most important factor of favorable outcome of treatment and life preservation for this complex group of patients.